Penyembelihan Hewan dan Jaminan Keamanan Pangan Dirasah kitab Nazam Tazkiyah Karya K.H. Ahmad Rifa'i (1786-1870) - Arif Al Wasim (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2015)
The number of people consumtions and needs of meet increses day by day. In order to gain a safe and legal (halal) meat, it is important to attend the slaughatering procces of the animal. The book of Nazam Tzkiyah is a guide book in animal slaughatering written by K.H, Ahmad Rifa'i in 1269 hijria (1852 CE). The study of the book is necessary to reveal the thought contribution of the Scholar of Nusantara in life practical aspect is meat safety and hygiene of hazardous material and germs, their inner aspect is meat legality and halal. Ethically, a person should not slaughter an animal before he or she understand the provisions of the shari`a and the procedures of slaughter, moreover animal slaughthering is carried out in order to worship by constantly seeking halal and avoiding haram. Integration of religious aspects and food quality control system should be pursued in order to improve the safety assurance animal origin foods system efficiency.